Evaluasi Kualitas Aplikasi Web Pemantau Menggunakan Model Pengujian Perangkat Lunak ISO/IEC 9126 - Condro Kartiko (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
The rapid growth of the world of information technology has an impact on the spread of the amount of software. Software maintenance is needed to support the quality of software. Software quality can be measured in terms of product and process.Some examples of the positive impact of improving software quality include benefits, reducing costs incurred for maintenance, and increasing productivity. One way to test the quality of the software is to use the ISO/IEC 9126 testing model by using fourcharacteristic assessments, namely usability, functionality, reliability, and efficiency. Case studies in this paper are web-based software application Social Media Monitoring and Online Media at PT. XYZ. The results of testing web-based software applications, social media, and online media monitoring belonging to PT. XYZ, using the ISO/IEC 9126 testing model get results, for the assessment of usability characteristics scored 61.81%.Assessment of usability characteristics used testing in the form of System Usability Scale (SUS). The characteristic assessment of functionality scored 76.55%. The characteristic assessment of functionality is carried out by software engineers with validation of the overall features. The characteristic assessment of reliability scored 99.14%. Assessment of reliability characteristics is carried out by calculating four variables, namely function, failure, working unit, and error rate. Finally, the characteristic assessment of efficiency scored 66.8%. Assessment of efficiency characteristics is done by performing calculations in the form of feature code, value, total weight grade, and HTTP request.